Countdown - Hagberg, David (New York : Tor, 1991)
When an American submarine and a Pershing missile vanish, a maverick C.I.A. agent must chase and catch a ruthless K.G.B. assassin before terrorism can strike at the balance of power.
National College of Business and Arts
Keywords: Spy stories; Thrillers (Fiction)